ACEH LANGUAGE LEARNING IMPLEMENTATION IN SMP NEGERI KOTA BANDA ACEH - H. Razali (Jurnal Serambi Ilmu, 2024)
The study is titled "Learning the Aceh language in Junior High School Kota Banda Aceh" aims to describe the implementation of language teaching in Junior High School Kota Banda Aceh. This research uses descriptive method and data collection was done by using interview, observation and documentation. Data source is the Teacherwho teaches language at Junior High School Kota Banda Aceh school year 2015/2016, and the principal. There are 3 Junior High School is a source of data that SMP 10, SMP 13 and SMP 17 the number of data sources six teachers and three principals. Data was collected through observation, interviews, public transportation and documentation. The results showed that the Aceh language learning is going well, but there are still many obstacles in its implementation. Barriers were mainly found on the Aceh language teachers themselves. Aceh language teachers still lack knowledge in the field of language Aceh. They are not the Aceh language studies teachers. In addition, the Aceh language teachers have not received education or training about the Aceh language learning. Furthermore, the availability of facilities and infrastructure of language learning is still lacking. In addition to lack of support for the school in the procurement Aceh language reading materials for both teachers and students. To cope with the materials teachers need to seek ways of teaching materials memfotocopi Aceh language. Similarly, teachers prepare Aceh language teaching and guided by the existing curriculum and learning tools to prepare.